The Relations of Knowledge and Attitude Towards Anaemia Among Petanque Athletes - Guruh Amir Putra; Muhammad Rachmat Kasmad; Nurussyariah Hammado (UNIVERSITAS NEGERI MAKASSAR, 2023)
Anaemia causes athletes to tire easily and decrease fitness due to physical activity, exercise, physiological and psychological stress, and environmental conditions. This study aimed to evaluate the knowledge and attitudes towards anaemia of petanque athletes in Makassar. A cross-sectional descriptive study, using a questionnaire, was conducted on thirty petanque athletes in Makassar. Descriptive statistics were used to elaborate on the demographic characteristics, knowledge, and attitude’s respondents. Pearson correlation was used to identify the relationship between variables. Seventeen (56.7%) male respondents with an average age of 21.53±4.13 years and thirteen (43.3%) female respondents with an average age of 20.08±2.12 years. There are 46.7% have moderate and 36.7% have poor knowledge about anaemia. Almost respondents (96.7%) have a slightly positive attitude regarding anaemia. A significant and positive correlation between knowledge-attitude (r=0.317, p<0.05) was observed. Conclusion: There is a significant relationship between knowledge and attitudes related to anaemia in petanque athletes. The positive and significant correlation reaffirms that better knowledge can lead to positive attitudes. This will further assist in the prevention and management of anaemia in sports. Therefore, an extensive health and sports education campaign should be provided to the general athlete population and petanque athletes.